Arching Propagation and Safety in Underground Mining - Melo-Hurtado, F; Vivanco-Avaria, F (Springer, 2023)
The transformation of large open pit mines into deep underground mines brings new challenges and difficulties that put the safety and operation of the mine at risk. The distribution and fluctuations of stress on the pillars and the arching are two of the main factors that influence the probability of suffering a catastrophic event in the mine. This article focuses on the study of the influence of the arching in creating a stress depletion zone that is identified with a dilation front, which in turn is ultimately responsible for the emergence of a cavity that propagates towards the upper surface of the system. Results indicate that significant arching occurs in the zones located above the active draw-points, while stress is concentrated around them. When single draw-point is operated the stress screening is significative because the large cavity created by the arching. This screening is dramatically reduced when two neighbouring draw-points are operated simultaneously. The increase in the size of the screening zone is associated with a decrease in the granular packing. By counterbalacing the particles flow from top surface we find a relationship between the cavity’s volume and the volume of removed material. A discussion of the effect of the operation method of two neighbouring draw-points on the effective arch size is included. © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature.